Workflow of a Preclinical Robotic Magnetic Resonance Imaging-guided Focused Ultrasound Body System - Nikolas Evripidou; Anastasia Antoniou; George Lazarou; Leonidas Georgiou; Antreas Chrysanthou; Cleanthis Ioannides; Christakis Damianou (Journal of Medical Ultrasound)
Background: Establishing an efficient workflow is crucial for the success of magnetic resonance-guided focused ultrasound (MRgFUS) procedures. The current study provides a comprehensive description of the workflow of a customized MRgFUS robotic body device for preclinical use and accompanied software through experiments in excised porcine tissue. Methods: The employed system comprises a single-element spherically focused transducer of 2.6 MHz that can be moved along four PC-controlled axes. A detailed description of essential software functionalities and its integration with a 3T Siemens magnetic resonance imaging (MRI) scanner through Access-I for interactive remote control of the scanner and real-time access to imaging data is provided. Following treatment planning on preoperative MR images, porcine tissue samples were sonicated in rectangular and irregular grid patterns with varying ultrasonic parameters and spatial step under software-based monitoring. Results: MRgFUS ablations of ex vivo porcine tissue were successfully performed utilizing a multimodal monitoring approach combining MRI-based temperature, thermal dose, and necrotic area mapping, thus demonstrating an efficient procedural workflow. The simulated necrotic regions were in excellent agreement with the actual lesions revealed upon tissue dissection and highly consistent with the planned sonication patterns. The software’s ability to accurately identify regions where necrosis did not occur and indicate to the user the specific points to be re-sonicated was demonstrated. Conclusion: Overall, the study highlights critical aspects in accurately planning and executing preclinical MRgFUS protocols within an efficient workflow. The provided data could serve as the basis for other researchers in the field.